2019
DOI: 10.21608/ejfs.2019.16364.1018
|View full text |Cite
|
Sign up to set email alerts
|

Carcass Characteristics and Nutritional Composition of Some Edible Chicken By-products

Abstract: T HE objective of this study was to evaluate the characteristics of chicken carcass and determine the nutritional composition of some edible chicken by-products, including liver, gizzard, wings, and skin. The total yield of liver, gizzard, wings and skinof chicken wasfound to be about 23.43%of carcassweight. The results showed that these chicken by-products are good sources of protein, fat, and minerals (ash). The greatest protein content was found to be26.33% (wb) for wings; while, skin showed the greatest fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 20 publications
(26 reference statements)
1
5
0
Order By: Relevance
“…Amongst the SFAs, palmitic acid (C16:0), arachidic acid (C20:0), and stearic acid (C18:0) were found to be dominant, whereas oleic acid (C18:1 n ‐9) and linoleic acid (C18:2 n ‐6) were the major USFAs in MC‐CG. Henry et al 12 . also reported that palmitic, stearic, oleic, and linoleic acids were dominant amongst all the fatty acids.…”
Section: Resultsmentioning
confidence: 94%
See 2 more Smart Citations
“…Amongst the SFAs, palmitic acid (C16:0), arachidic acid (C20:0), and stearic acid (C18:0) were found to be dominant, whereas oleic acid (C18:1 n ‐9) and linoleic acid (C18:2 n ‐6) were the major USFAs in MC‐CG. Henry et al 12 . also reported that palmitic, stearic, oleic, and linoleic acids were dominant amongst all the fatty acids.…”
Section: Resultsmentioning
confidence: 94%
“…Owing to their functional groups, these free hydrophobic amino acids have been reported to exhibit strong antioxidant activity 31 . The free hydrophobic amino acids are also known to facilitate the reachability of antioxidant peptides at the hydrophilic zone, 6 and F‐CGH had considerable amounts of the essential amino acids (200.24 g kg −1 of protein) that quality meat products should contain 12 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Beef liver ( Soladoye et al, 2022 ), chicken liver ( Henry et al, 2019 ), and pork liver ( Mora et al, 2019 ) are utilized in many processed foods and have been studied extensively. However, the literature on mutton and fish livers is scarce.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, the Egyptian government had supported broiler farming and their industry to withstand protein sufficiency. Yearly, chicken consumption is about 1.2 billion broilers in Egypt, which is equivalent to broiler meat of 1125 million tons (Henry et al, 2019). In addition, the total consumption of broilers in Egypt is probable to increase from 993,000 tons in 2017 to 1,156,000 tons in 2026 (FAO, 2017).…”
Section: Introductionmentioning
confidence: 99%